On combining wavelet-based designed filters and an adaptive mimic filter for phasor estimation in digital relaying - Silva, Kleber M.; Küsel, Bernard F. (Electric power systems research, 2012)
► A novel phasor estimation algorithm is proposed. ► Orthogonal full-cycle filters with adaptive filtering of the decaying DC component. ► Filters combine the MODWT with the least error square algorithm. ► Decaying DC component elimination with an adaptive digital mimic filter. ► Excellent results compared to other full cycle algorithms. A phasor estimation algorithm, which uses orthogonal full-cycle filters in conjunction with an adaptive filtering of the decaying DC component, is presented in this paper. The full-cycle orthogonal filters are designed using a technique which combines the maximum overlap discrete wavelet transform and the least error square algorithm. The decaying DC component elimination is performed using an adaptive digital mimic filter. The frequency and time responses of the proposed algorithm are compared with those of other full cycle algorithms reported in the literature on the subject. The obtained results reveal that the proposed algorithm rejects all harmonics, is less sensitive to interharmonics, presents better transient responses and can be faster than other full cycle algorithms.